Debate on Muhkamât and Mutasyahabihat A Study of Quraish Shihab’ Thought - Sukamta Sukamta (Sunan Kalijaga: International Journal of Islamic Civilization, 2022)
The current paper is dedicated to examine Quraish Shihab’s views on Muhkamât and Mutasyahabihat. The method applied in this study is critical analysis by comparing various reference of his works. I am interested in this topic because it is related to the Qur’anic Studies. I found that not all muhkamat verses are disputed, some of them remained clear. In the discussion around the texts of the mutasyabihat, Quraish Shihab did not mention the views of sufi thought such as Ibn Arabi who used the 'irfani’s perspective. In addition, his study of mutasyabihat verses related to God's attributes and deeds can be found deeper in other works, by using an intertextual analysis. It is found that Quraish Shihab did not relate majaz when he discussed it. The majaz style in the Qur'an, among others, is used to expand the function of the language description, to accommodate as many ideas or meanings as possible, by giving a picture or imagination in such a way as to be understood by man, as a being to whom the Qur'an is derived. Since the verses are addressed to humans to understand, the symbols used also in the form of language understood by humans.